Fatigue behavior of different geometry scaffolds for bone replacement - Baptista, Ricardo (2019)
When transplanting bone tissue is not a possibility, tissue engineering is responsible for developing solutions to substitute the functions of the missing bone structure or support the process of bone regeneration. Scaffolds can be used to fulfill this mission by supporting loads that were applied to the missing bone, supporting the cell regenerating process, allowing for the necessary nutrients and oxygen diffusion and delivering growth factors or drugs. Scaffold geometry design must support static and dynamic loads up to 20 MPa in order to replace human trabecular bone. Also, it should generate macro and micro pores to support cell growth and mineral precipitation, while all pores should be interconnected for nutrient and oxygen diffusion. Scaffolds were fabricated according to ASTM-695 standard, using two different layouts, 50% porosity and a theoretical distance of 0.8 mm between each filament. A 400 µm diameter nozzle was used, and scaffolds were produced at 215 ºC with deposition rate of 30 mm/s. Both designs were fatigue tested until 3600 cycles, using different load amplitudes and a frequency of 0.25 Hz. The orthogonal scaffold showed improved behavior, with compression modulus reaching 680 MPa, when a maximum stress of 14.5 MPa was applied.